Surgery for Partial Seizures and Cortical Dysplasia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The role of ictal or continuous epileptogenic discharges (I/CEDs), recorded during intraoperative electrocorticography (ECoG), in the planning of surgical resection for patients with cortical dysplastic lesions (CDyLs) and intractable partial seizures was evaluated at the Montreal Neurological Institute, the Epilepsy Surgery Program, Porto-Alegre, Brazil, and the Chonbuk National Hospital, Chonju, Korea.